The Relations between Parenting Patterns and the Implementation of the Learning Process for Children aged 5-6 Years - Laelillah, Resty Hasby; Purwani, Annisa; Enjang, Enjang (International Conference on Islamic Studies, 2022)
In essence, parenting is the interaction of parents and children, parents encourage children by changing behavior, knowledge, and values ​​that are considered most appropriate for children. The learning process is an active process because knowledge is formed from learning objects. The purpose of this study is to determine the characteristics of parenting styles, children's learning processes and to analyze whether there is a significant relationship between parenting styles and children's learning processes in KB Az-Zahra. This study uses a quantitative descriptive correlation approach, which is a research method that looks at the form of the relationship between variables. The sample in this study amounted to 28. The types of data taken were grouped into two categories, namely primary data and secondary data. Data collection techniques using respondent questionnaires, observation sheets, and documentation. The results of the research from the data that have been analyzed can be concluded that the average parenting pattern of 58.40% is categorized as quite good, while the results of the average learning process are 75.27% categorized as good. The relationship between parenting patterns and the learning process of this child has a correlation value of 0.618 with a correlation percentage of 38.2% and is categorized as a relationship between parenting styles and the learning process. So that parenting patterns have a real relationship to the learning process of children aged 5-6 years.